1977
DOI: 10.1007/bf01434062
|View full text |Cite
|
Sign up to set email alerts
|

The141Eu nuclide and its decay properties

Abstract: The nuclide 141Eu is identified to have two beta decaying isomers, ~41gEu and ~4~mEu, whose decay half-lives are measured to be 40.0_+0.7s and 3.3_+0.3s, respectively. Their decay properties are studied by means of beta and gamma spectroscopy techniques. The states with J~ assignments in *4~Sm thus deduced are compared with those of the other odd-A, N=79 isotones. The total decay energy of ~gEu is measured to be 6.03_+0.10 MeV, which is compared with the predictions of several mass formulae and with the decay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…The 139Eu nuclide was first identified by Westgaard et al [3] and they found it to decay with a half-life of 22__ 3 s. Subsequently, van Klinken and Feenstra [4] reported that its decay populates primarily the 11/2-, 457.4keV isomeric state of 139Sm (139mSm) and they thus assigned a J~= 11/2-to the ground state of 139Eu. However, nuclear systematics indicate that the decay properties of 139Eu should resemble those of 11/2-141mEu, which we studied previously [5]. This implies that the decay of 139Eu would also populate several other relatively high spin states in 1398m and this has been borne out in the present work.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…The 139Eu nuclide was first identified by Westgaard et al [3] and they found it to decay with a half-life of 22__ 3 s. Subsequently, van Klinken and Feenstra [4] reported that its decay populates primarily the 11/2-, 457.4keV isomeric state of 139Sm (139mSm) and they thus assigned a J~= 11/2-to the ground state of 139Eu. However, nuclear systematics indicate that the decay properties of 139Eu should resemble those of 11/2-141mEu, which we studied previously [5]. This implies that the decay of 139Eu would also populate several other relatively high spin states in 1398m and this has been borne out in the present work.…”
Section: Introductionmentioning
confidence: 60%
“…At this energy the interferring activities unavoidably produced were exactly those we encountered in our study of the decay properties of ~39gSm [2]. Almost all of these unwanted activities came from the decay of 142m'gEU [8], 141m'gEu [5], 141m'gSm [9], 14~ [10], 1398m [2], ~38Pm [1] and 137pm [11]. The decay properties of these nuclides are well known from the references cited.…”
Section: Experimental Techniquesmentioning
confidence: 93%
“…The assignment of the spin 11/2-for the 22s lelGd is tentative. This scheme is likely based on the 3.3s isomeric state of 14~Eu located at 96.5 keV [23]. As a matter of fact, a 96.5 keV transition is weakly observed in the single He-jet spectra with a half-life roughly estimated to be of the order of 10s which could consist in a mixing of 22s and 3.3s activities due to a simultaneous production of 14~Gd and 141mgu.…”
Section: A= 138 Mass Chainmentioning
confidence: 97%
“…The data acquisition was started 20 s after the bombardment in order to allow shorter-lived activities to decay substantially. Several well known contaminating activities were also inevitably produced, either directly or as daughter activities, at this bombardment energy: 145 g, mGd [22,23], 144Gd [24], a43 g, mGd [25,26], 143Eu [2], a42g'mEu [3], 14lg'mEu [8], 141g'mSm [7,27], 14~ [13,28], 139g'mSm [11,12] la9 Pm [9] and 138Pm [10]. Several lines from the decay of ~42Gd that were clearly observed in the X-y coincidences were thus strongly contaminated in the y-ray singles spectrum.…”
Section: Resultsmentioning
confidence: 99%